Comparison of the Chinese schema and the International Antigenic Typing System for serotyping Pseudomonas aeruginosa. - Liu, P V (1987)
Twelve strains of Pseudomonas aeruginosa representing 12 serogroups in the serogrouping schema used in the People's Republic of China were compared with serogroups in the International Antigenic Typing System (IATS). The first eight groups originated in the People's Republic of China, and group II appears to have a new major antigen that is not found in the IATS. Groups I, III, IV, V, VI, VII, and VIII correspond to groups 11, 6, 9, 4, 8, 3, and 1, respectively, of the IATS. Groups IX, X, XI, and XII are immunotypes 3, 4, 5, and 1, respectively, of Fisher et al. (M. W. Fisher, H. B. Devlin, and F. J. Gnabasik, J. Bacteriol., 98:835-836, 1969); they exhibited a wide range of serological cross-reactions but correspond mainly to IATS groups 2, 3, 10, and 6, respectively.